EVALUASI PROGRAM BIMBINGAN KONSELING DENGAN MENGGUNAKAN MODEL EVALUASI DISCREPANCY DI SMP KRISTEN 2 EBEN HAEZER SALATIGA - Andianti, Yohana Putri; Dwikurnaningsih, Yari; Loekmono , J.T. Lobby (Universitas Pendidikan Mandalika, 2025)
The purpose of this research is to evaluate the guidance and counseling (BK) program at SMP Kristen 2 Eben Haezer Salatiga. This research uses the discrepancy evaluation model, which has 5 steps. The research was conducted using data and source triangulation. The principal, guidance counselor, and students are the subjects of the research. Observation, documentation, and thorough interviews were used to collect data. The research results show that there is a difference between the ideal standards of the BK program and its implementation in the field. This is especially true for service planning, activity implementation, and program evaluation. This study found that the BK program at SMP Kristen 2 Eben Haezer Salatiga needs to be improved in terms of planning, implementation, and evaluation to be more efficient and meet the needs of the students.